Exploring the Anticorrosion Performance of 2-(((4-Chlorobenzyl) Thiol) Methyl)-1H-Benzo[d]imidazole on Aluminum in 1 M HNO3 - T. H. Rokia; Tigori, M. A.; Koffi, A. A.; Niamien, P. M. (Journal of Scientific Research, 2024)
Organic corrosion inhibitors play a vital role in controlling and reducing corrosion. It is in this context that 2-(((4-chlorobenzyl) thiol) methyl)-1H-benzo[d]imidazole was inspected as an inhibitor of aluminum corrosion in HNO3 medium. Gravimetric techniques and density functional theory (DFT) were conducted to prove the inhibition activity of this compound. Experimental results indicate that the inhibition potency of this compound increases with its concentration and decreases with increasing temperature. Indeed, the maximum inhibition efficiency reaches 97.74 % at concentration Cinh=5.10-3 M and at temperature T = 298 K. Adsorption isotherms study indicates that there is a strong interaction between the particles adsorbed on metal surface with adsorbed layer stability. The adsorption process is dominated by physical adsorption with increased disorder. Activated thermodynamic parameters were calculated and examined. Theoretical data derived from DFT calculations explained the adsorption process of the compound to metal surface. These theoretical data are consistent with the experimental results.